Factors Determining Consumers Intention to Shop Online in Greater Jakarta - Lucy Tanurahardja; Yudi; Budi; Mohamad Rosidi; Louis Tirtomoyo Santoso (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2020)
Online shopping is increasingly becoming a favorite activity for city dwellers who are smartphones users as a means to fulfil their necessities. Increasingly, people obtain their needs through online shopping and retailers are working hard to increase their sales by winning consumers to shop at their online stores. In this paper, we investigate factors affecting consumer’s intention in online shopping in Greater Jakarta area. These factors includes trust, perceived risk, reference group, behavioral control awareness, business competency, usefulness and convenience, brand image, and promotion. 272 respondents participated in this survey and their responses were documented using Likert scales. After data collection, a Factor Analysis used to identify correlations between variables and Regression Analysis techniques were used to identify significant factors. Our research findings reveal that out of eight factors, four factors affect consumers’ intention to shop online. These factors, starting from the most significant, are promotion, brand image, usefulness and convenience, and business competency